2005
DOI: 10.1080/02656730400001108
|View full text |Cite
|
Sign up to set email alerts
|

RF tumour ablation: Computer simulation and mathematical modelling of the effects of electrical and thermal conductivity

Abstract: This study determined the effects of thermal conductivity on RF ablation tissue heating using mathematical modelling and computer simulations of RF heating coupled to thermal transport. Computer simulation of the Bio-Heat equation coupled with temperature-dependent solutions for RF electric fields (ETherm) was used to generate temperature profiles 2 cm away from a 3 cm internally-cooled electrode. Multiple conditions of clinically relevant electrical conductivities (0.07-12 S m-1) and 'tumour' radius (5-30 mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The difference between normal and cancer tissue is especially pronounced in the breast due to the high fat content of breast tissue [9] and a recent modelling study suggested taking advantage of this difference to preferentially ablate breast tumours but not surrounding tissue [10]. For RF tumour ablation, two recent modelling studies have shown that differences in electrical conductivity between tumour and surrounding normal tissue significantly affect tissue heating [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…The difference between normal and cancer tissue is especially pronounced in the breast due to the high fat content of breast tissue [9] and a recent modelling study suggested taking advantage of this difference to preferentially ablate breast tumours but not surrounding tissue [10]. For RF tumour ablation, two recent modelling studies have shown that differences in electrical conductivity between tumour and surrounding normal tissue significantly affect tissue heating [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…To date, computer studies on RFA have examined the effect of specific factors related to the procedure and different modeling approaches [4][5][6][7][8][9][10][11]. None have focused on a direct comparison of different experimental results in terms of coagulation zone size and the evolution of electrical variables.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In some cases, the model simply reduces the applied voltage to the maximum level at which no tissue is heated beyond 100ºC [4][5][6]. Others do not provide details of the RF power delivery protocol [7], so we cannot be sure whether an impedance-controlled pulsing protocol was really modeled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models have been developed to simulate the temperature distributions of tissue during the treatment [4,[23][24][25][26]. The complexity of the tumor composition, the influence of heterogeneous electrical conductivity, thermal conductivity, blood perfusion rate, and the specific distribution of blood vessels on the results have been studied [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%